PENGARUH STRATEGI PEMBELAJARAN DAN KEMAMPUAN BERPIKIR KRITIS TERHADAP HASIL BELAJAR SOSIOLOGI MAHASISWA - Muzakar, Abdullah; Tohri, Ahmad; Asror, M Zainul (Universitas Hamzanwadi, 2022)
Appropriate learning strategies and critical thinking skills affect student learning outcomes. This study aims to examine the effect of learning strategies on group investigation and direct instruction with the ability to think critically on student learning outcomes in the subject of Industrial Sociology. This research was conducted with true-experimental techniques in 2 classes of students. The total sample of this study were 45 students. This research data collection uses two methods: tests and questionnaires. Data analysis using descriptive and inferential two-way ANAVA 2 x 2 techniques. The results showed that the results of the Dunnet t test for different mean learning strategies was significant (sig. = .000 ˂ ɑ = .05), the critical thinking skills level was significant (sig. = .000 ˂ ɑ = .05), and learning outcomes was significant (sig. = .000 ˂ ɑ = .05). In classes that are treated and the ability to think critically high, high learning outcomes. Thus it was concluded that the learning strategy of group investigation and the level of critical thinking ability was very influential in improving the students learning outcomes of the Sociology Education Study Program at Hamzanwadi University Semester IV Academic Year 2018/2019, in the Industrial Sociology subject.